Development and microbiological characterization of ricotta seasoned with oregano and garlic - Santiago Beltrão, Fabiana Augusta (2020)
Ricotta is a product of Italian origin manufactured using acid precipitation to separate whey proteins. The ricotta can be consumed in its natural state, with or without salt, and savored with honey, sugar or fruit, or seasoned with garlic, parsley, oregano and others. The objective of this work was to process and evaluate ricotta added with different concentrations of garlic and oregano and to evaluate its microbiological stability. Four formulations were prepared: traditional ricotta (T1); ricotta seasoned with oregano (T2); ricotta seasoned with garlic (T3) and ricotta seasoned with garlic and oregano (T4), which were submitted to microbiological analysis after 10 days of cold storage (5 ± 2 ºC). The results of the microbiological analyzes indicated that all samples were within the standards established by current legislation for high moisture cheeses.